Pengaruh Asimetri Informasi, Penghindaran Pajak, Dan Ukuran Perusahaan Terhadap Manajemen Laba - Indah Paramita; Eka Rima Prasetya (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effect of information asymmetry, tax avoidance and company size on earnings management in primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The sampling method used in this study uses the purposive sampling method, with a quantitative research type. The data used is secondary data, namely the company's annual financial report. The number of samples used in this study was 23 primary consumer goods sector companies with observations for 5 (five) years, so that 115 observation objects were selected. The analysis method used is panel data regression with the help of Eviews version 12 software. The results of the study show that partially, information asymmetry does not affect earnings management, tax avoidance does not affect earnings management, while company size affects earnings management. However, simultaneously, the three independent variables have a significant effect together on earnings management.